Alkynyl−B(dan)s in Various Palladium‐Catalyzed Carbon−Carbon Bond‐Forming Reactions Leading to Internal Alkynes, 1, 4‐Enynes, Ynones, and Multiply Substituted Alkenes. Issue 8 (28th February 2019) - Tani, Tomohiro; Sawatsugawa, Yuuki; Sano, Yusuke; Hirataka, Yo; Takahashi, Naomi; Hashimoto, Sadahiro; Sugiura, Tetsuya; Tsuchimoto, Teruhisa
Abstract: It was found that the C( sp )−B(dan) bond of alkynyl−B(dan)s can be directly used for palladium‐catalyzed carbon−carbon bond‐forming reactions with aryl(alkenyl) halides and allylic carbonates as electrophiles, thus delivering unsymmetrical internal alkynes and unconjugated 1, 4‐enynes, respectively. With acyl chlorides as electrophiles, ynone synthesis is also promoted by a palladium catalyst with the assistance of a copper co‐catalyst. These reactions can be achieved as more convenient one‐pot reactions, without isolating the alkynyl−B(dan) formed in situ by the zinc‐catalyzed dehydrogenative borylation of alkynes with HB(dan). In addition to direct C( sp )−B(dan) bond transformations, the C≡C bond in an alkynyl−B(dan) proved to be a promising scaffold for the construction of a multisubstituted alkene, which is synthesized by diboration of the C≡C−B(dan) moiety, leading to a triborylalkene followed by iterative regio‐ and stereoselective Suzuki−Miyaura cross‐coupling reactions. As one example, the synthesis of the ethene with four different aryl groups, p‐ MeC6 H4, p‐ MeOC6 H4, p‐ NCC6 H4, and p‐ F3 CC6 H4, was attained in high overall yield of 64% in six steps starting from the terminal alkyne, p‐ MeC6 H4 C≡CH. Besides these synthetic applications of the alkynyl−B(dan), the scope of the alkynyl substrate in the zinc‐catalyzed dehydrogenative borylation was expanded to enhance the reliability as a provider of the alkynyl−B(dan). Consequently, 42 alkynes were found to participate in the dehydrogenative borylation as substrates; these are alkyl‐, alkenyl‐, aryl‐, heteroaryl‐, ferrocenyl‐, silyl‐, and borylalkynes, with or without a variety of functional groups. Lastly, a new method for preparing HB(dan), as a sulfide‐free, cost‐saving, and reaction‐time‐saving route, is disclosed. Abstract :